MANAGEMENT OF MENTAL NURSING CARE WITH SERVICE EXCELLENCE FOR Mr. M WITH LOW SELF-ESTEEM AT PROF. DR. MUHAMMAD ILDREM MENTAL HOSPITAL MEDAN - fatemaluo, Yartina; Herna Rinayani Manurung; Rolasnih Lilista Simbolon; Rotua Margaretta Sihombing; Roy Miracle Sidauruk; Tiamri Lubis; Nurhayati (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
ABSTRACT Mental health is an essential aspect of an individual’s life, encompassing mental, emotional, and social well-being. One common disorder observed in patients with mental illness is low self-esteem, which can affect their social, psychological, and emotional functioning. Schizophrenia is a severe mental disorder characterized by symptoms such as hallucinations, delusions, and affective disturbances, often accompanied by low self-esteem. This study aims to examine the management of psychiatric nursing care using a service excellence approach for Mr. M, a patient experiencing low self-esteem at Prof. Dr. Muhammad Ildrem Mental Hospital in North Sumatra Province, in the year 2025. This research employs a case study approach based on the six stages of the nursing process: assessment, diagnosis, planning, implementation, evaluation, and documentation. The primary focus is on applying the principles of service excellence in providing nursing care to patients with low self-esteem. Through the service excellence approach, the nursing student was able to conduct a comprehensive assessment, establish an accurate nursing diagnosis, plan individualized interventions, carry out nursing actions according to the patient’s needs, and perform proper evaluation and documentation. Nursing care delivered professionally and humanely has proven effective in gradually improving the patient’s self-esteem. The service excellence approach in managing psychiatric nursing care for patients with low self-esteem has been proven effective in enhancing the patient’s psychosocial condition. This study is expected to contribute to improving the quality of mental health nursing services, particularlyat Prof. Dr. Muhammad Ildrem Mental Hospital.